Case study of two Iraqi patients with Mucopolysaccharidosis (Hurler syndrome "type I" and Maroteaux-Lamy syndrome "type VI") treated with Hematopoietic Stem Cell Transplantation (HSCT) - Furqan M. Abdulelah; Mohammed M. Mohammed; Rabab Hassan Baaker (College of Pharmacy / Mustansiriyah University, 2023)
Mucopolysaccharidosis I (MPS I) or Hurler and Mucopolysaccharidosis VI (MPS VI) or Maroteaux-Lamy syndrome are infrequent genetic disorder inherited as an autosomal recessive disease attributed to genetic   variants genetic variant causing α-L iduronidase (IDUA) and arylsulfatase B (ARSB)enzyme deficiency, respectively.  Here, two cases of children suffering from MPS disorder were described, the first case was MPS I while the second case was MPS VI and both cases were treated with allogenic Hematopoietic Stem Cell Transplantation approach in order to limit skeletal deterioration and retard neurocognitive alterations and hence, improve the quality of life of affected children. Following Transplantations outcomes reveal a full engraftment of donor cells as well as improvement of recipient enzymatic activity, enzyme replacement therapy post-transplantation will augment transplantation clinical outcomes. Transplantation will be more successful if the disease diagnosed early before the severe irreversible symptoms ensue.